Risk factors related to congenital hypothyroidism: Systematic review and Meta-analysis - Boutaina Boumehdi; Mochhoury Latifa; Elkhoudri Noureddine; Chahboune Mohamed; Elyahyaoui Sofia; Chebabe Milouda (Journal of Biostatistics and Epidemiology)
Introduction: Congenital endocrine disorders have a global impact on the morbidity and mortality of children and are a public health problem that heavily affects society and the daily lives of affected children and their families. The severity and consequences of congenital hypothyroidism (CH) on physical and especially cerebral maturation combined with lifetime mental retardation make CH neonatal screening one of the costliest preventive health programs. Thus, early diagnosis can improve the prognosis of the disease. The objective of the study is to examine CH’s risk factors reported in previous studies.